The Individuality of the Protagonist in the Works of Normurad Norkobilov Interpretation of Nature - Bektashovich, Bazarov Sobirjon (European Journal of Life Safety and Stability (2660-9630), 2021)
The article seeks to interpret the individual nature of the protagonist in the works of Normurad Norkobilov, to psychologically describe the protagonist and to show the peculiarities of human nature through his experiences and psyche